E.E. Just Goes Digital during COVID-19 - Dieuwertje J. Kast; Tara Treiber; Dijanna Figueroa; Lynn Whitley (Current: The Journal of Marine Education, 2021)
The Bridge Builders Foundation’s Ernest Everett Just (E.E. Just) Youth Science Program is designed to expose minority (Black/African American and Latinx) students to careers and academic pursuits in STEM in a hands-on and inquiry-based way. COVID-19, or the novel coronavirus, tried to put a rift in the Summer Marine Science Camp, but the Bridge Builders Foundation did a strategic pivot and engaged a group of partner marine educators to be creative and build a lesson plan and provide instruction to give participating students a hands-on and engaging experience in the digital realm. Using a variety of digital tools and hands-on activities, the educators provided students with a Summer Marine Science Camp experience right in their own homes. One of the hands-on activities even included shipping materials directly to students so they could be the model designers. Pre-Post survey results showed program success in students’ interest and enthusiasm for the program, as well as their conceptual knowledge gain. As part of the data collection and analysis process, we calculated the ‘learning gains’ from the course. A learning gain shows the improvement between the pre-and post-learning assessment scores. Students showed a 41% normalized learning gain, above the 30% minimum significant gain.